1990
DOI: 10.3109/02699059009026147
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial sequelae of closed head injury: Effects on the marital relationship

Abstract: Head injury frequently produces physical and psychological sequelae involving cognitive, behavioural, and personality disturbances which are chronic and perhaps even permanent. Clinically, it is apparent that the marital relationships of head injury patients face initial disruption as well as ongoing challenges in dealing with the physical, neuropsychological, and emotional changes post-injury. However, there is little empirical data to substantiate these observations. In this study, the marital relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 14 publications
3
49
1
2
Order By: Relevance
“…They thus fail to distinguish between strains on the marital, as opposed to the parental relationship [70]. As a result, literature that specifically examines spouses' psychological adjustment following TBI is scant [38].…”
Section: Differential Impact On Spouses and Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…They thus fail to distinguish between strains on the marital, as opposed to the parental relationship [70]. As a result, literature that specifically examines spouses' psychological adjustment following TBI is scant [38].…”
Section: Differential Impact On Spouses and Parentsmentioning
confidence: 99%
“…Moore and his colleagues are among the few researchers who have conducted works in the area of post-TBI marital relationships [12,70,75,76].…”
Section: Marital Relationship Following Tbimentioning
confidence: 99%
“…15 In contrast, Peters et al reported that people with spinal cord and head injury experienced adjustment difficulties through their marital relationships. 16 In Iran, there is little information about the life transition by marriage in post SCI life. The prevalence and the point prevalence of traumatic SCI in Tehran, the capital of Iran, was reported from 1.2 to 11.4 and 4.4 (95% CI, 1.2-11.4) per 10,000 people, respectively.…”
mentioning
confidence: 99%
“…La détresse psychologique de l'aidant est également reliée à d'autres types de changements tels que ceux se produisant dans les modes relationnels (Fengler & Goodrich, 1979;Kreutzer et al, 1994a;Lefebvre et al, 2004;Peters, Stambrook, Moore & Esses, 1990;Rosenbaum & Najenson, 1976) et dans les rôles tenus par les membres de la famille (Fengler & Goodrich, 1979;Gan, Campbell, Gemeinhardt & McFadden, 2006;Hallet, Zasler, Maurer, & Cash, 1992;Marsh et al, 1998a;Marsh et al, 2002;Rosenbaum & Najenson, 1976). Les victimes et leurs aidants éprouvent beaucoup de difficultés à maintenir des relations familiales et sociales (Lefebvre et al, 2004).…”
Section: Le Bouleversement Des Rôles Sociaux Et Familiaux Chez La Vicunclassified
“…En ce qui concerne la vie de couple, les moments d'intimité et la satisfaction conjugale sont souvent réduits à leur minimum (Douglas & Spellacy, 2000;Peters et al, 1990). Les conjointes dont le mari a subi un TCC décrivent généralement ce dernier comme étant entêté, immature et dépendant (Rosenbaum & Najenson, 1976 (Chwalisz, 1996).…”
Section: Le Bouleversement Des Rôles Sociaux Et Familiaux Chez La Vicunclassified